Film mulching counteracts the adverse effects of mild moisture deficiency, and improves the quality and yield of Cyperus esculentus. L grass and tuber in the oasis area of Tarim Basin - Ding, Ya; Zhang, Zhihao; Lu, Yan; Li, Li; Islam, Waqar; Zeng, Fanjiang (Frontiers in Plant Science, 2024)
Introduction Plastic film mulching (PFM) and deficit irrigation (DI) are vital water-saving approaches in arid agriculture. Cyperus esculentus is a significant crop in dry zones. However, scant data exists on the impacts of these water-saving methods on C. esculentus yield and quality. Method Using randomized block experiment design. Three irrigation strategies were tested: CK (standard irrigation), RW20 (20% water reduction), and RW40 (40% water reduction). Mulchin treatments included film mulching (FM) and no film mulching (NFM). Results Results revealed substantial effects of film mulching and drip irrigation on soil nutrients and physical properties, with minor influence on grass, root, and tuber stoichiometry. PF treatment, DI treatments, and their interaction significantly affected C. esculentus forage and tuber yields. Initially, grass and tuber yields increased and then decreased with reduced irrigation. The highest yields were under RW20 (3716.31 and 4758.19 kg/ha). FM increased grass and tuber yield by 17.99% and 8.46%, respectively, over NFM. The water reduction augmented the biomass distribuiton of the leaf and root, while reducing the tuber biomass in NFM. FM significantely impacted grass ether extract content, while reduced water influenced grass and tuber crude protein and tuber ether extract content. Mild water stress increased ether extract, crude protein, and soluble matter in grass and tubers, while excessive RW decreased them. Conclusion Integrating soil traits, nutrients, yield, and quality, findings indicate C. esculentus yield and quality primarily hinge on soil water content, pond hydrogenase, and electrical conductivity. Based on this results, the recommended strategy is to reduce irrigation by 20% for cultivating C. esculentus in this area.